IDENTIFICAÇÃO DO POLIMORFISMO rs9939609 DO GENE FTO EM PACIENTES SUBMETIDOS À CIRURGIA BARIÁTRICA EM UM HOSPITAL PRIVADO DE SÃO LUÍS - MA. - DINIZ, Iagho José Lima (2022)
According to the WHO, obesity is defined as the “abnormal or excessive accumulation of fat that presents a health risk”. In recent years, extensive research has shown the contribution of genetics to the development of obesity, and to date, the strongest association in the entire genome related to obesity is the rs9939609 polymorphism of the FTO gene, with the risk genotype of allele A, especially when in homozygosity. The study aimed to evaluate the relationship between the rs9939609 polymorphism and weight loss in patients undergoing bariatric surgery. The observational, analytical and prospective cohort study included 44 patients undergoing bariatric surgery in a private hospital in São Luís, Maranhão. Anthropometric and sociodemographic data were collected directly from medical records. Genetic material was extracted from saliva samples collected from patients and molecular analysis was evaluated by TaqMan probes in quantitative PCR (qPCR). The experiments took place at the Tumor and DNA Bank of Maranhão – BTMA/UFMA. Most participants were female (68.2%), predominantly brown (63.6%), with higher education (59.1%), married/stable union (63.6%). Regarding clinical data, most patients were not diabetic (77.3%), without arterial hypertension (65.9%), dyspnea (79.5%), and hepatic steatosis (75%). The most used surgical method was the Sleeve type (54.5%). Genetic analysis showed that 10 participants (22%) had the FTO gene rs993609 polymorphism in homozygosity (AA), 17 (39%) were heterozygous (AT) and 17 (39%) had the wild type (TT) genotype. There was no statistically significant difference between patients carrying the polymorphic A allele (AA/AT) and those with the wild-type allele (TT) concerning anthropometric data. However, the presence of diabetes mellitus was significantly more prevalent in patients with the rs9939609 polymorphism. Regarding the reduction in BMI after surgery, all patients had a similar decrease in body mass index, with no genotype influence.